Microwave radiation-induced grafting of 2-methacryloyloxyethyl trimethyl ammonium chloride onto lentil extract (LE-g-DMC) as an emerging high-performance plant-based grafted coagulant - Chua S.C.; Chong F.K.; Ul Mustafa M.R.; Mohamed Kutty S.R.; Sujarwo W.; Abdul Malek M.; Show P.L.; Ho Y.C. (Nature Research, 2023)
plant extract; trimethylammonium salt derivative; chemistry; infrared spectroscopy; lentil; microwave radiation; theoretical model; Lens Plant; Microwaves; Models, Theoretical; Plant Extracts; Spectroscopy, Fourier Transform Infrared; Trimethyl Ammonium Compounds